Endovascular Aneurysm Sealing for Infrarenal Abdominal Aortic Aneurysms: 30-Day Outcomes of 105 Patients in a Single Centre. Issue 2 (August 2015) - Brownrigg, J.R.W.; de Bruin, J.L.; Rossi, L.; Karthikesalingam, A.; Patterson, B.; Holt, P.J.; Hinchliffe, R.H.; Morgan, R.; Loftus, I.M.; Thompson, M.M.
Abstract : Objective: Endovascular aneurysm sealing (EVAS) has been proposed as a novel alternative to endovascular aneurysm repair (EVAR) in patients with infrarenal abdominal aortic aneurysms (AAA). The early clinical experience, technical refinements, and learning curve of EVAS in the treatment of AAA at a single institution are presented. Methods: One-hundred and five patients were treated with EVAS between March 2013 and November 2014. Prospective data were recorded on consecutive patients receiving EVAS. Data included demographics, preoperative aneurysm morphology, and 30-day outcomes, including rates of endoleak, limb occlusion, reintervention, and death. Postoperative imaging consisted of duplex ultrasound and computed tomographic angiography. Results: The mean age of the cohort was 76 ± 8 years and 12% were female. Adverse neck morphology was present in 72 (69%) patients, including aneurysm neck length <10 mm (20%), neck diameter >32 mm (18%), β-angulation >60° (21%), and conical aneurysm neck (51%). There was one death within 30 days. The incidence of Type 1 endoleak within 30 days was 4% ( n  = 4); all were treated successfully with transcatheter embolisation. All four proximal endoleaks were associated with technical issues that resulted in procedure refinement, and all were in patients with adverse proximal aortic necks. The persistent Type 1 endoleak rate at 30 days was 0% and there were no Type 2 or Type 3 endoleaks. Angioplasty and adjunctive stenting were performed for postoperative limb stenosis in three patients (3%). Conclusions: EVAS appears to be associated with reasonable 30-day outcomes despite the necessity of procedural evolution in the early adoption of this technique. EVAS appears to be applicable to patients with challenging aortic morphology and endoleak rates should reduce with procedural experience. The utility of EVAS will be defined by the durability of the device in long-term follow-up, although the absence of Type 2 endoleaks is encouraging.